The Effect of the Degree of Misfit Between Human Resources Management Practices and the Types of Organizational Culture on Organizational Performance - Gugup Kismono; Raden Muhammad Pradana Ramadista (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
“Fit model” argues that the level of misfit between human resources management (HRM) practices and the type of organizational culture negatively influences organizational performance. However, the lack of emprirical research to support that contention can be problematic. Utilizing the concept of fit, this study aims to examine empirically the effect of the degree of misfit between HRM practices and the types of organizational cultures on organizational performance. Data were collected from a sample comprising of 128 respondents representing 64 companies in Indonesia, from nine industrial sectors. The hypothetical model was developed based on four types of HRM practices (human relations, internal process, rational goals, and open systems) and four types of organizational cultures (clan, hierarchy, market, and adhocracy). Euclidean distance scores were calculated to describe the misfit between the HRM practices and the types of organizational culture variables. Subsequently, the effect of the misfit scores on organizational performance was determined. The results show that the degree of misfit between HRM practices and the type of organizational culture has a significant and negative effect on organizational performance. This empirical research supports the concept of fit, in which the type of organizational culture that is supported by suitable HRM practices will result in a more positive organizational performance. Then, it is deemed necessary for companies to adapt their HRM practices to their culture, in order to improve their performance.